Acute toxicity and health-related quality of life after accelerated whole breast irradiation in 5 fractions with simultaneous integrated boost - Van Hulle, Hans (Breast, 2020)
INTRODUCTION: Acceleration of radiotherapy in 5 fractions for breast cancer can reduce the burden of treatment. We report on acute toxicity after whole-breast irradiation with a simultaneous integrated boost in 5 fractions over 10–12 days. MATERIAL AND METHODS: Acute toxicity and health-related quality of life (HRQoL) of 200 patients, randomized between a 15- or 5-fractions schedule, were collected, using the CTCAE toxicity scoring system, the Multidimensional Fatigue Inventory, EORTC QLQ-C30 and BR23 and the BREAST-Q questionnaire. The prescribed dose to the breast was either 15∗2.67 Gy (40.05 Gy) or 5∗5.7 Gy (28.5 Gy). 90% of patients received a SIB to a cumulative dose of 46.8 Gy (15∗3.12 Gy) or 31 Gy (5∗6.2 Gy). RESULTS: Physician-assessed toxicity was lower for the 5-fractions group. A significant difference was observed for breast pain (p = 0.002), fatigue (p < 0.0001), breast edema (p = 0.001) and dermatitis (p = 0.003). Patients treated in 5 fractions reported better mean HRQoL scores for breast symptoms (p = 0.001) and physical well-being (p = 0.001). A clinically important deterioration in HRQoL of 10 points or more was also less frequently observed in the latter group for physical functioning (p = 0.0005), social functioning (p = 0.0007), fatigue (p = 0.003), breast symptoms (p = 0.0002) and physical well-being (p = 0.002). CONCLUSION: In this single institute study, acute toxicity of accelerated breast radiotherapy in 5 fractions over 10–12 days seems to compare favourably to hypofractionated breast radiotherapy in 15 fractions. Less breast edema, dermatitis, desquamation, breast pain and fatigue are seen. Social and physical functioning are also less disturbed and patients have a better future perspective.